The effects of NAA and precursors on growth and the phytochemical constituents of Elaeis guineensis jacq. embryoid cultures / Zati Hanani Termizi - Termizi, Zati Hanani (2017)
Elaeis guineensis Jacq. (oil palm) is a very important commercial crop in Malaysia. This plant is a valuable source of oil and phytochemical compounds used in food, cosmetics, pharmaceuticals and biofuels. Conventional propagation of oil palm cannot be done vegetatively since it has a single growing apex. Hence, propagation in vitro has great advantages in the case of oil palm where vegetative propagation is possible only via tissue culture. Somatic embryogenesis is an important pathway for the oil palm in vitro propagation in order to increase the number of new regenerated plantlets.